PELAKSANAAN PROGRAM PENGEMBANGAN KEWIRAUSAHAAN DAN KEUNGGULAN KOMPETITIF UMKM DI DINAS KOPERASI UMKM PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN KUANTAN SINGINGI - Sriwahyuni, Popi; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Micro, Small and Medium Enterprises  play an important role in the economy of Kuantan Singingi Regency, especially in driving economic activities, increasing income and providing employment opportunities. The policy in implementing the UMKM development program by the Ministry of Industry and Trade of the UMKM Cooperative, Kuantan Singingi Regency is a program of entrepreneurship development and competitive advantage of MSMEs which includes training, coaching and providing assistance to MSME players. This study aims to determine the implementation of entrepreneurship and competitive development programs for MSMEs and to determine the inhibiting factors. This research uses theoryGeorge R. Terry in Manullang (2012:8), Planning (Planning),Organizing (Organizing),Implementation (Actuating),Supervision (Controlling).This research uses qualitative methods and documentation. The findings in this study indicate that the implementation of the Micro, Small and Medium Enterprises development program in Kuantan Singi Regency has not been optimal. This is indicated by the lack of mastery and application of technology by MSME actors, they prefer manual equipment, besides that, MSME actors.still not paying attention to financial management properly.Keywords: Management, Program Implementation, Micro, Small and Medium Enterprises